The Effect of Interactive Videos on Introducing English Vocabulary to Early Childhood - Novitasari, Yesi; Mahira, Nisa; Fadillah, Siti; Atika Putri, Azlin; Wahyuni, Sri (Universitas Lancang Kuning, 2025)
This study aims to determine whether interactive videos can introduce English vocabulary to children aged 5-6 years in Group B at Pelita Hati Kids Kindergarten, Pekanbaru. The type of research used is experimental research. The subjects of this study were 30 children aged 5-6 years. Data collection techniques included observation and documentation. The data analysis techniques used were normality tests, homogeneity tests, and hypothesis testing. The results of this study show an improvement in learning through interactive videos, as seen from the average pre-test and post-test scores: the average listening pre-test and post-test scores were 2.35 and 3.90, respectively; the average speaking pre-test and post-test scores were 1.58 and 2.92; and the average writing pre-test and post-test scores were 1.47 and 2.58. Thus, these aspects can be improved through the use of interactive videos